Pavspl Expression Dynamics in Fruits and Seeds and in Relation to Endocarp Lignification Status During the Transition from Development to Ripening in Sweet Cherry - Maldonado-Soto, J (Multidisciplinary Digital Publishing Institute (MDPI), 2025)
The transition to ripening in non-climacteric species is governed by several signals, including hormones that enhance or counteract the abscisic acid (ABA)-promoting effect. The SQUAMOSA Promoter-binding protein-Like (SPL) transcription factors are involved in ripening through the modulation of anthocyanin biosynthesis. In sweet cherry fruits, several miR156-targeted PavSPLs are expressed before and during ripening. Recently, some PavSPLs were found in the transition from development to ripening in cultivars contrasting in maturity time. Additionally, several forms of miR156 were expressed in sweet cherry seeds of an early-season cultivar. In this work, we addressed the relevance of endocarp lignification and PavSPLs expression for the transition to ripening. First, we characterized early- and late-season sweet cherry cultivars, ‘Celeste’ and ‘Regina’, focusing on fruit and seed development, endocarp lignification, and PavSPL expression profile. Fruit growth dynamics revealed an earlier onset of color development and lignification in ‘Celeste’, while ‘Regina’ exhibited a prolonged lag phase and delayed embryo development. Transcript profiling at the light green stage showed a higher expression of PavSPL genes in fruits and identified cultivar-specific expressions, especially between ‘Regina’ and ‘Celeste’ seeds. Co-expression networks linked PavSPLs to genes involved in lignin and anthocyanin biosynthesis. We focused on PavSPL2 and PavSPL9, which were targeted by mtr-miR156a and gma-miR156f. Both PavSPLs and miRNAs were expressed in fruits and seeds at the yellow stage, an advanced point in the transition to ripening in sweet cherry. Exogenous application of auxin-related compounds in the mid-season cultivar ‘Lapins’ modulated endocarp lignification and pigmentation. Notably, p-IBA treatment, which enzymatically targets the lignin pathway, transiently increased anthocyanin accumulation and reduced lignin deposition, effects that correlated with the downregulation of PavSPL gene expression. These findings highlight the interplay between lignification, color evolution, and pigment biosynthesis during the transition from development to ripening in sweet cherry fruits, and suggest a role for PavSPL genes in this transition. © 2025 by the authors.